Reading syllable-spaced versus word-spaced text in Hmong Daw: breaking up isn't so hard to do. Issue 2 (2nd July 2016) - Vitrano-Wilson, Seth
ABSTRACT: Three experiments were performed to compare people reading word-spaced texts and syllable-spaced texts in Hmong Daw, using the Latin-script orthography known as RPA. The results showed no overall difference in reading speed between the two spacing styles when reading naturally connected stories, but did show advantages to syllable spacing when words were presented in isolation, and for sentences with polysyllabic words that had not appeared previously in the test. The results are contrary to the common untested assumption among linguists involved in orthography development that word spacing is the optimal spacing choice for all languages, and suggest that syllable spacing is a valid option for certain languages in the right sociolinguistic situations. The results also underline the importance of the syllable level for cognitive processing during reading.